Metabolic reprogramming and immune microenvironment characteristics in laryngeal carcinoma: advances in immunotherapy - Ma, Kexin; Mao, Qingjie; Fei, Bing; Ni, Tingting; Zhang, Zhenxin; Ni, Haosheng (Frontiers in Immunology, 2025)
Laryngeal squamous cell carcinoma (LSCC) is a prevalent malignancy with high mortality and recurrence rates, necessitating novel therapeutic strategies. Recent research highlights the pivotal role of metabolic reprogramming and immune microenvironment alterations in LSCC pathogenesis, providing promising avenues for targeted therapy. This review summarizes the metabolic characteristics of LSCC, including glycolysis, lipid metabolism, and amino acid biosynthesis, and their implications for tumor progression and therapeutic resistance. Additionally, this review further describes the tumor microenvironment’s immunosuppressive landscape, including immune checkpoint regulation, tumor-associated macrophages, and T-cell dysfunction. The integration of metabolic and immune-targeted strategies represents a promising frontier in LSCC treatment, warranting further investigation.